2020
DOI: 10.3390/pathogens9030180
|View full text |Cite
|
Sign up to set email alerts
|

Immune Phenotype and Functionality of Mtb-Specific T-Cells in HIV/TB Co-Infected Patients on Antiretroviral Treatment

Abstract: The performance of host blood-based biomarkers for tuberculosis (TB) in HIV-infected patients on antiretroviral therapy (ART) has not been fully assessed. We evaluated the immune phenotype and functionality of antigen-specific T-cell responses in HIV positive (+) participants with TB (n = 12) compared to HIV negative (−) participants with either TB (n = 9) or latent TB infection (LTBI) (n = 9). We show that the cytokine profile of Mtb-specific CD4+ T-cells in participants with TB, regardless of HIV status, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Immune responses influence the outcome of any disease, and an increased number of CD16 + and NK cells in the HHCs is associated with LTBI (41). In TB endemic countries, NK cell phenotypes and functional profiles are modified, and these immune phenotypes can be used for the diagnosis of TB (42)(43)(44). We found significantly higher numbers of CD16-expressing CD14 + cells and CCR7-expressing CD3 -CD56 + CD27 + memory-like NK cells in nonconverters than in converters at baseline (Figure 1B), suggesting that the immune cell phenotype can play a role in resistance to TB in nonconverters.…”
Section: Discussionmentioning
confidence: 99%
“…Immune responses influence the outcome of any disease, and an increased number of CD16 + and NK cells in the HHCs is associated with LTBI (41). In TB endemic countries, NK cell phenotypes and functional profiles are modified, and these immune phenotypes can be used for the diagnosis of TB (42)(43)(44). We found significantly higher numbers of CD16-expressing CD14 + cells and CCR7-expressing CD3 -CD56 + CD27 + memory-like NK cells in nonconverters than in converters at baseline (Figure 1B), suggesting that the immune cell phenotype can play a role in resistance to TB in nonconverters.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-infected patients presenting with advanced immunodeficiency, assessment of TB-specific T-cell responses may be compromised. However, it has been demonstrated that CD38, HLA-DR and Ki-67 are appropriate markers for the discrimination of TB infection and TB disease in HIV-infected TB patients with moderate immunodeficiency [12,31]. Future investigations need to include cohorts of patients with HIV infection and advanced immunodeficiency as well as otherwise immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the activation of M.tb-specific T cells is an active field to develop TB immunodiagnosis, for example looking at CD4 + IFN-g + T cells for HLA-DR, CD38, and Ki-67 markers, which shows 100% sensitivity and 95% specificity for active TB (86)(87)(88). Phenotypic changes on M.tb-specific CD4 T cells are also used as surrogate markers for TB treatment efficacy and can help to discriminate between TB (profile: CD38 pos , CD27 low ), treated TB (CD38 neg , CD27 low ), and LTBI (CD38 neg , CD27 high ) (89).…”
Section: Immunodiagnostics Of Latent Mtb Infection (Ltbi)mentioning
confidence: 99%